2021
DOI: 10.1515/geo-2020-0318
|View full text |Cite
|
Sign up to set email alerts
|

Elemental geochemistry of the Middle Jurassic shales in the northern Qaidam Basin, northwestern China: Constraints for tectonics and paleoclimate

Abstract: The elemental geochemical characteristics of mudstones/shales are good tracers for indicating the evolution of tectonics, paleoenvironment, and paleoclimate. Based on the continuous sampling of drilling cores from the Middle Jurassic Dameigou and Shimengou Formations in the northern Qaidam Basin, the major, trace, and rare earth elements of the 31 mudstones and shales were analyzed. The information on the evolution of tectonics, provenance, and paleoclimate during Middle Jurassic was also recovered. The result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…This indicates that the structural complexity of the western study area is higher than that of the eastern area mainly due to the different influences of regional geological context. Specially, both orogenic belts, including Altun strike-slip fault and Qilian Mountain, affect the western area, whereas only Qilian Mountain affects the eastern area, resulting in more complex coal reservoirs and strata structural complexity. The average D 2 of Saishiteng and Yuqia coalfields in the west is 2.88, and the mean D 2 of Quanji and Delingha coalfields in the east is 2.68. Compared with D 1 and D 2 data, it can be found that the fractal dimension D 1 has a little change and a high correlation coefficient, whereas the fractal dimension D 2 is significantly different, and the D 2 of type III with a weak hysteresis loop is significantly lower than that of type I and type II with an obvious hysteresis ring (Tables and ).…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that the structural complexity of the western study area is higher than that of the eastern area mainly due to the different influences of regional geological context. Specially, both orogenic belts, including Altun strike-slip fault and Qilian Mountain, affect the western area, whereas only Qilian Mountain affects the eastern area, resulting in more complex coal reservoirs and strata structural complexity. The average D 2 of Saishiteng and Yuqia coalfields in the west is 2.88, and the mean D 2 of Quanji and Delingha coalfields in the east is 2.68. Compared with D 1 and D 2 data, it can be found that the fractal dimension D 1 has a little change and a high correlation coefficient, whereas the fractal dimension D 2 is significantly different, and the D 2 of type III with a weak hysteresis loop is significantly lower than that of type I and type II with an obvious hysteresis ring (Tables and ).…”
Section: Discussionmentioning
confidence: 99%